PENGARUH DIMENSI KUALITAS PELAYANAN TERHADAP KEPUASAN WISATAWAN KULINER BUBULAK TEPI SAWAH DI KOTA BOGOR - Sekti Rahardjo; Aminudin; Sri Endah Yuwantiningrum (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2023)
This research aims to find out whether service quality (X) influences the level of tourist satisfaction (Y) at the Bubulak culinary tourism on the edge of the rice fields, Bogor City. The population in this study was 859 people using the Slovin formula calculation to obtain a sample size of 90 people which was added to 100 people. Sampling in this research used probability sampling. In this research, the data analysis technique used is a simple linear regression test. The results of the research show that there is a simultaneous influence of service quality (X) on customer satisfaction (Y). Service quality (X) has an influence of 75.8% on customer satisfaction (Y) while the other 24.2% is influenced by other factors.